2018
DOI: 10.1001/jamaophthalmol.2018.0376
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Colorado Retinopathy of Prematurity Screening Model

Abstract: The Colorado Retinopathy of Prematurity (CO-ROP) model uses birth weight, gestational age, and weight gain at the first month of life (WG-28) to predict risk of severe retinopathy of prematurity (ROP). In previous validation studies, the model performed very well, predicting virtually all cases of severe ROP and potentially reducing the number of infants who need ROP examinations, warranting validation in a larger, more diverse population. OBJECTIVE To validate the performance of the CO-ROP model in a large mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 42 publications
1
23
1
Order By: Relevance
“…Still, more than 20% of infants would pass unscreened, which is unacceptable. Furthermore, if only the criterion of net weight gain in 28 days had been used for ROP screening in our study, the number of examined children would have decreased by only 2%, which is significantly less than the figure reported for the CO-ROP [16][17][18] (~23%) or WIN-ROP (~75%) algorithm 28 . The reason for this low percentage was the generally higher prevalence of any form of ROP in our cohort.…”
Section: Fig 3 Box and Whisker Plot Of Net Weight Gain (Nwg) In Thecontrasting
confidence: 65%
See 1 more Smart Citation
“…Still, more than 20% of infants would pass unscreened, which is unacceptable. Furthermore, if only the criterion of net weight gain in 28 days had been used for ROP screening in our study, the number of examined children would have decreased by only 2%, which is significantly less than the figure reported for the CO-ROP [16][17][18] (~23%) or WIN-ROP (~75%) algorithm 28 . The reason for this low percentage was the generally higher prevalence of any form of ROP in our cohort.…”
Section: Fig 3 Box and Whisker Plot Of Net Weight Gain (Nwg) In Thecontrasting
confidence: 65%
“…The model assesses ROP through a combination of the following three criteria: GA ≤30 weeks, BW ≤1500 g, and net weight gain of ≤650 g between birth and 4 weeks of age. Both original 17 and validation 16,18 studies demonstrated high sensitivity in predicting ROP, rendering CO-ROP a good tool for reducing the number of examinations.…”
Section: Introductionmentioning
confidence: 99%
“…Although various studies have been conducted from a clinical perspective to prevent blindness caused by ROP, including the identification of risk factors, development of predictive models, and diagnosis of the disease stage with artificial intelligence [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ], this review will focus on the translational research that has progressed from basic research to clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Although some models have been validated and exhibited excellent predictive performance, the validation cohorts consisted mainly of infants in highly developed countries [11][12][13][14][15][16][17][18][19]. Nevertheless, the data gathered from less-developed countries are scarce but indispensable.…”
Section: Introductionmentioning
confidence: 99%